Case Report: Streptococcus alactolyticus as a Rare Pathogen of Mitral Endocarditis - Vinciguerra, Mattia; Santamaria, Valeria; Romiti, Silvia; D'Abramo, Mizar; Toto, Gianmarco; De Bellis, Antonio; Taliani, Gloria; Sangiorgi, Giuseppe; Greco, Ernesto (Frontiers in Cardiovascular Medicine, 2021)
Streptococcus Bovis/Streptococcus equinus complex (SBSEC) is a group of non-enterococcal group D Streptococci that colonizes both humans and animals. Due to gastrointestinal disease they can switch in opportunistic pathogens passing through intestinal mucosal barrier and may cause bacteremia and distant organs damage. Despite Infective Endocarditis (IE), extra-cardiac manifestations of organs damage include osteoarticular infections, meningitis and biliary infections among others, moreover the association with colonic pathological lesions has been largely described. Streptococcus Alactolyticus as species included in SBSEC may share pathophysiological similarities, although it represents an extremely rare cause of distant organ infections, being reported in literature as causative agent of IE in only two other cases. We describe a case of 69-year-old male admitted to our Institution due to mild-moderate dyspnea and fever, affected by cervico-brachialgia for three weeks. Streptococcus Alactolyticus was identified as causative agent of Infective Endocarditis on mitral valve, causing severe regurgitation.